HOW TO IMPLEMENT FAIR TRADE IN INDONESIA - Yovita Dhevi Sylviana (Universitas Jenderal Ahmad Yani, 2018)
Fair trade is one of the trading system that concern about the fairness and the development of the small producers that tend to be treated unfairly by free trade system since the main idea of competitive advantage from free trade incline to be exploitative towards these small producers. Indonesia has many small producers, artisans and farmers that do trading with international society, therefore, fair trade is supposed to be one of a beneficial trading system that Indonesia should implement. But the fact is that, fair trade is not developed well in Indonesia, even many NGOs and fair trade organization went bankrupt in Indonesia. One of the fair trade organization that still do well and have been categorized as success in implementing the fair trade system is APIKRI, a fair trade organization in craft industry that located in the special region of Yogyakarta. In this paper, we argue that based on APIKRI success, it’s not impossible to implement the fair trade system in Indonesia that will bring a beneficial result to the majority of Indonesian producers which are the small producers, artisans and farmer.